2017
DOI: 10.18203/2349-3291.ijcp20172699
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric lymphadenopathy in children with recurrent abdominal pain

Abstract: Background: Enlarged mesenteric lymph nodes (MLN) are frequently seen in children with abdominal pain and in the absence of other disorders, have been attributed to primary mesenteric lymphadenitis. Mesenteric lymphadenitis is commonly reported in children with acute, chronic or recurrent abdominal pain and no evidence of other pathologies. The purpose of this study was to find out the association of USG finding of enlarged mesenteric lymph nodes with causation of recurrent abdominal pain and outcome of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In our study we found that children who had presented with fever along with pain abdomen had a higher incidence of having mesenteric lymphadenitis which is probably suggestive that an infective/inflammatory pathology as a cause for mesenteric lymphadenopathy and this corresponding to previous studies where they found upper respiratory infection as a common cause for the enlarged mesenteric lymph nodes. [7][8][9] In our study we also found the basic inflammatory markers to be elevated in children with mesenteric lymphadenitis which is suggestive of the same (Table 3).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In our study we found that children who had presented with fever along with pain abdomen had a higher incidence of having mesenteric lymphadenitis which is probably suggestive that an infective/inflammatory pathology as a cause for mesenteric lymphadenopathy and this corresponding to previous studies where they found upper respiratory infection as a common cause for the enlarged mesenteric lymph nodes. [7][8][9] In our study we also found the basic inflammatory markers to be elevated in children with mesenteric lymphadenitis which is suggestive of the same (Table 3).…”
Section: Discussionsupporting
confidence: 74%
“…The inclusion criteria were all children between the age of 1-12 presenting to the outpatient department (OPD)/emergency with pain abdomen and ultrasonographic diagnosis of mesenteric lymphadenitis was based on the criteria of three or more lymph nodes that are each 5 mm or greater in the short axis. 8 Acute pain abdomen was defined as pain abdomen of fewer than 48 hours duration. An institutional questionnaire was developed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While varying reports of mesenteric adenitis exist in the global literature, by and large, its possibility as a cause of abdominal symptoms cannot be ignored. [2][3][4] Often considered, the most frequent clinical mask of acute appendicitis, mesenteric adenitis can mimic a variety of conditions including intussusceptions and gastroenteritis. [5][6][7] From earliest considerations that included tuberculosis as an etiological factor to a routinely recommended appendectomy, much seems to have evolved in its management now that a definitive pre-operative diagnosis is possible in most situations.…”
Section: Discussionmentioning
confidence: 99%